2014
DOI: 10.14740/jcgo264w
|View full text |Cite
|
Sign up to set email alerts
|

Does Lower Uterine Segment Involvement in Grade 3 Endometrial Cancer Impact Recurrence Patterns and Patient Outcomes?

Abstract: Background: The aim of the study was to determine the impact of lower uterine segment (LUS) on progression free survival (PFS), recurrence patterns and outcomes in women with high-grade endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Clark et al [21] and Kogan et al [22] found that there is a significant association between LUS Involvement and FIGO stage in Grade 3 Endometrial Cancer. Kogan et al [22] found that there is a significant association between LUS involvement and FIGO stage in type II endometrial cancer and the unique mutational profile of serous tumors.…”
Section: Table 4: the Association Between Lower Uterine Segment Invol...mentioning
confidence: 99%
“…Clark et al [21] and Kogan et al [22] found that there is a significant association between LUS Involvement and FIGO stage in Grade 3 Endometrial Cancer. Kogan et al [22] found that there is a significant association between LUS involvement and FIGO stage in type II endometrial cancer and the unique mutational profile of serous tumors.…”
Section: Table 4: the Association Between Lower Uterine Segment Invol...mentioning
confidence: 99%